Opini Warganet mengenai Moderasi Beragama dalam Percakapan Twitter - Nurhayani Saragih; Suraya (Dakwah Institut PTIQ Jakarta, 2022)
The purpose of the study was to describe the opinions of influencers in netizen conversations on Twitter regarding religious moderation. The research uses public opinion, agenda setting models, and the spiral of silence to analyze opinions and topics discussed by Mega influencers, Macro influencers, Micro influencers, and Nano influencers. This study uses a qualitative approach with a descriptive content analysis method. Research data obtained using NVivo with the keyword religious moderation. Research results: Most of the public opinion of influencers on twitter are positive. In the account of the nano-influencer, 11 accounts have a negative tone, and 1 account has a neutral tone regarding religious moderation. This study concludes that religious moderation is a government agenda that is socialized through the Ministry of Religion of the Republic of Indonesia and all its staff. The parties who have different opinions, only a small part express their disapproval of the religious moderation program through Twitter.